Acute peritonitis caused by a ruptured urachal cyst accompanied by omphalitis in an adult: a case report and literature review - Myeong Gon Cho; Hyun-Young Han; Joo Heon Kim; Moon-Soo Lee (Journal of Minimally Invasive Surgery)
Omphalitis is an infection of the umbilicus that can cause inflammation to spread. Omphalitis is rare in adults; however, it can occasionally occur owing to urachal remnants. A 61-year-old male patient with abdominal pain and umbilical pus was admitted to the emergency room. Abdominal computed tomography revealed peritonitis with multiple intra-abdominal abscesses. The patient was diagnosed with peritonitis resulting from urachal cyst rupture. Laparoscopic drainage of the abscesses and excising of the umbilicus and intra-abdominal fistula tract were performed. Antibiotics were administered, and the patient was discharged uneventfully. The rarity of peritonitis caused by infection and urachal cyst rupture can make diagnosing omphalitis challenging. Therefore, in this case report and literature review, we discuss the diagnosis and treatment of complicated omphalitis, which rarely progresses to peritonitis owing to ruptured urachal cysts.